Weak intervention backfire and criminal hormesis: why some otherwise effective crime prevention interventions can fail at low doses - Linning, Shannon J. (The British journal of criminology, 2018)
Although crime prevention tactics are designed to reduce offending, some studies have revealed instances where reported crime actually increases after introducing lower intensity interventions. An analogous trend—characterized by low-dose stimulation and high-dose inhibition—called hormesis has already been observed in the natural sciences. We argue that this phenomenon is theoretically applicable to crime prevention. Findings suggest that researchers should test varying intensities of interventions to avoid rejecting ones that would be otherwise effective at higher levels. Research using dose–response techniques and simulation models should be explored to determine whether a weak intervention backfire effect occurred or is possible. Knowledge of such information could lead to more effective crime prevention strategies and better specified analytic models for evaluation.